La differenza attraverso le immagini - Cannonieri, Igor (Scenari, 2021)
The theme of the image is addressed here by recovering the perspective (historical-critical) lines of the problem and then referring to the work of J. Derrida. The aim is not only to show the contribution of the French philosopher to the discussion about the visible arts, but also to go beyond this, in order to grasp the scope of the great questions that are at the heart of deconstruction: overcoming of the traditional notion of origin; trace; supplement; difference; and logocentrism.